Proteomic analysis of the Papaya-Fusarium equiseti interaction: understanding mode of infection and plant response at the molecular level - Karunamoorthy, Jeevindramoorthy; Allawi, Mohammed Yahya; Al-Taie, Bilal Salim; Jambari, Nuzul Noorahya; Rahmad, Norasfaliza; Rahman, Norafizah Abdul; Kamaruddin, Nurhaida; Al-Obaidi, Jameel R. (Academic Press, 2025)
Papaya (Carica papaya L.) is an important tropical fruit with significant nutritional and economic value. However, postharvest diseases, particularly caused by Fusarium equiseti, result in severe quality losses. This study aims to elucidate the molecular mechanisms underlying papaya's response to F. equiseti infection using a proteomic approach. Papaya fruits were divided into control and Fusarium-challenged groups. Proteins were extracted from both groups and analyzed through two-dimensional gel electrophoresis (2-DE) followed by MALDI-ToF/ToF MS/MS for protein identification. Differentially expressed proteins were identified and mapped using protein-protein interaction networks. A total of 1250 protein spots were detected, with 8 significantly altered between the control and infected fruits successfully identified. Key upregulated proteins included Linoleate 9S-lipoxygenase, involved in lipid metabolism, and 30S Ribosomal Protein S3, associated with protein synthesis. Conversely, proteins like the stromal Heat Shock-Related Protein were downregulated, suggesting compromised stress responses during infection. These results provide a glimpse into the intricate defence mechanisms in papaya, revealing extensive changes primarily at the translational level involving stimulation of lipid metabolism and increased ribosomal activity to combat Fusarium infection. It gives insight into probable molecular targets for the intensification of disease resistance in papaya. Further investigations are recommended to elucidate the different contributions of these proteins and then enhance management strategies for postharvest diseases.